Adapting the Educational Values of Islamic Boarding Schools in Instilling Religious Character - Hamidah, Aam Siti; Muslimah, Revi (International Conference on Elementary Education, 2025)
The Elementary School StudentsElementary school students are at an age with a very critical developmental phase so they can accept any values and behavior from the environment around them. Apart from that, the problem with children today is due to a lack of internal religious values schools, many of which do not practice moral and religious values good (Raharja & Nurachadija, 2023). Therefore, religious and moral education is a strong foundation building a solid character foundation for the future(Aiena, 2023). This research aims to 1) analyze the religious character of Islamic boarding school students, 2) analyze character values in Islamic boarding school educational institutions, and 3) describe the results of implementing character values in Islamic boarding school institutions in schools. The method used is a qualitative descriptive method with analytical techniques Miles & Huberman whichincludes 1) data reduction, 2) data presentation and 3) drawing Conclusion. The results of this research show that students at school can accept the teachings of religious character values applied by teachers. The hope is that over time, students' religious character will stick and develop as a foundation for students' character in the future